Author Correction: ID3 regulates the MDC1-mediated DNA damage response in order to maintain genome stability - Jung-Hee Lee (Nature Portfolio, 2018)
This Article contains errors in Fig. 3, Fig. 4 and Fig. 7, for which we apologize. In Fig. 3, panel ‘b’, the 0.5 hour time point after Ku55933 treatment images were inadvertently replaced with duplicates of the 3 hour time point after Ku55933 treatment images in Fig. 3b. Additionally, in panel ‘b’, the 0.5 hour time point after Nu7026 treatment images were inadvertently replaced with duplicates of the 180 min time point after siMDC1 treatment images in Fig. 3d. In Fig. 4, panel ‘g’, RNF168 foci in U2OS cell images were inadvertently replaced with duplicates of RNF168 foci in HeLa cell images in Fig. 4f. In Fig. 7, panel ‘b’, the DAPI images 0.5 hours after IR under siID3 treatment were inadvertently replaced with DAPI images of a different field of view from the same experiment. Additionally, in panel ‘i’, the shID3 mock-treated GFP-ID3 cells image was inadvertently replace with duplications of the shID3 mock-treated GFP-ID3 cells image in Fig. 7g.